The Contribution of Microglia to the Development and Maturation of the Visual System - Dixon, Michael A.; Greferath, Ursula; Fletcher, Erica L.; Jobling, Andrew I. (Frontiers in Cellular Neuroscience, 2021)
Microglia, the resident immune cells of the central nervous system were once considered quiescent cells that sat in readiness for reacting to disease and injury. Over the last decade, however, it has become clear that microglia play important roles in maintaining the normal nervous system. The retina is an easily accessible part of the central nervous system and therefore much has been learned about the function of microglia from studies in the retina and visual system. Anatomically, microglia have processes that contact all synapses within the retina, as well as blood vessels in the major vascular plexuses. Microglia contribute to development of the visual system by contributing to neurogenesis, maturation of cone photoreceptors, as well as refining synaptic contacts. They can respond to neural signals and in turn release a range of cytokines and neurotrophic factors that have downstream consequences on neural function. Moreover, in light of their extensive contact with blood vessels, they are also important for regulation of vascular development and integrity. This review summarizes what we have learned about the role of microglia in maintaining the normal visual system and how this has helped in understanding their role in the central nervous system more broadly.